Transforming Poverty Alleviation Policies: Adapting the Regional Innovation Architecture Approach (Jurnal Bina Praja, 2024)
Poverty, defined as the inability of individuals to fulfill their basic needs, poses a significant challenge to achieving community welfare in many regions. Addressing this challenge requires a holistic and integrated approach that considers Indonesian society's diverse cultural and socio-economic contexts. Adapting innovative architecture is crucial in confronting Indonesia's various cultural and socio-economic landscapes. This approach provides new alternatives for regional development strategies and opens up new opportunities for transforming and adapting innovation to tackle poverty holistically and sustainably. This research aims to restructure innovation architecture and examine its potential to transform regions in poverty alleviation efforts. The study employs a qualitative research method with a literature review analysis. It explores novel approaches for developing a solution-oriented and applicable analysis and recommendations for communities. Additionally, the research analyzes several regions that have successfully implemented regional innovation and reduced local poverty levels. Data is collected through a literature search strongly relevant to the research objectives. The findings indicate that innovation architecture can drive regional transformation in poverty alleviation through 1) Enhancing collaboration and synergy among stakeholders, 2) Creating a conducive innovation ecosystem, and 3) Developing contextual and sustainable innovative solutions. These findings demonstrate the substantial potential of innovation architecture in transforming regions to achieve poverty alleviation. This aligns with existing theories emphasizing stakeholder collaboration and synergy as key factors in creating effective, innovative solutions. Innovation architecture can serve as an effective tool in transforming regions towards poverty alleviation. Proper and sustainable implementation of innovation architecture can assist regions in crafting contextual, innovative solutions and enhancing community welfare.
Keywords: Collaboration; Innovation Architecture; Innovative Solutions; Poverty Alleviation; Regional Transformation